Follow-up of Acute Respiratory Disorders in Cyclists Competing in the 100th Giro d’Italia - Pollastri, Luca; Macaluso, Claudio; Vinetti, Giovanni; Tredici, Giovanni; Lanfranconi, Francesca (International Journal of Sports Medicine, 2020)
Acute respiratory disorder is a common sub-clinical condition affecting elite cyclists. Monitoring the perturbations of the immunological cells in the respiratory tract, indicative of a likely proinflammatory state, during an International Cycling Union world tour is a challenging task. The aim of this study was to follow up on the sign and symptoms of upper way respiratory infections with or without asthma, using non-invasive methods, during a 21-day race (100° Giro d’Italia, 2017). Nine male elite cyclists of the Bahrain Merida Team were evaluated before the training season and daily during the race. Clinical history, skin prick and spirometric test, acute respiratory symptoms were measured using validated questionnaires, and values of fraction of exhaled nitric oxide were collected longitudinally. Four of the 9 athletes had allergies with/or consistent abnormal spirometric curves before the race. During the race, 5 athletes had a fraction of exhaled nitric oxide values >20 ppb which correlated with respiratory symptoms collected through questionnaires. These were related to the environmental characteristics of the places travelled through in the race. The athletes with a predisposition to chronic respiratory inflammation in the pre-competitive season were more likely to develop acute respiratory symptoms during the race.
Keywords: exercise; FeNO; cycling; WURSS-21; airway inflammatory response; URTI